Factors associated with early progression of non‐small‐cell lung cancer treated by epidermal growth factor receptor tyrosine‐kinase inhibitors. (10th January 2014) - Rozensztajn, Nathalie; Ruppert, Anne‐Marie; Lavole, Armelle; Leprieur, Etienne Giroux; Duruisseaux, Michael; Vieira, Thibault; Rabbe, Nathalie; Lacave, Roger; Antoine, Martine; Cadranel, Jacques; Wislez, Marie
Abstract Epidermal growth factor receptor tyrosine‐kinase inhibitors (EGFR‐TKI) are a therapeutic option as second‐line therapy in non‐small‐cell lung carcinoma (NSCLC), regardless of the EGFR gene status. Identifying patients with early progression during EGFR‐TKI treatment will help clinicians to choose the best regimen, TKI or chemotherapy. From a prospective database, all patients treated with gefitinib or erlotinib between 2001 and 2010 were retrospectively reviewed. Patients were classified into two groups according to their tumor response by RECIST after 45 days of treatment, progressive disease (PD) or controlled disease (CD). Two hundred and sixty‐eight patients were treated with EGFR‐TKI, among whom 239 were classified as PD (n = 75) and CD (n = 164). Median overall survival was 77 days (95% CI 61–109) for PD and 385 days (95% CI 267–481) for CD. Patients with PD were of younger age (P = 0.004) and more frequently current smokers (P = 0.001) had more frequently a performance status ≥2 (P = 0.012), a weight loss ≥10% (P = 0.025), a shorter time since diagnosis (P < 0.0001), a pathological classification as non‐otherwise‐specified NSCLC (P = 0.01), and the presence of abdominal metastases (P = 0.008). In multivariate analysis, abdominal metastases were the only factor associated with early progression (odds ratio (OR) 2.17, 95% CI [1.12–4.19]; P = 0.021). Wild‐type EGFR versus mutated EGFR was associated with early progression. The presence of abdominal metastasis was independently associated with early progression in metastatic NSCLC receiving EGFR‐TKI.